2009
DOI: 10.2355/tetsutohagane.95.340
|View full text |Cite
|
Sign up to set email alerts
|

Plate-out Behaviors of O/W Emulsions for Cold Rolling in a Short Time Interval

Abstract: Synopsis : O/W emulsions are widely used in tandem cold rolling mills as coolants, in order to reduce friction forces and prevent heat scratches. The lubricating properties may be determined by various factors, and the amount of plated out oil on strip surface is one of the important ones, as well as dynamic concentration mechanics of emulsions at inlet of roll bite, on which much interest has been paid since 1970s. However, plate-out oil film formation has been recognized as a quite important factor in produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The lubricating properties of emulsion liquids have been extensively studied by researchers and engineers in the field of tribology [1][2][3]. Emulsions composed of water and oil are employed as the metalworking fluid in various operations such as rolling, cutting, ironing, and grinding [1][2][3][4][5]. In steel-making industries, spray jet impingement of O/W emulsions is widely used in cold rolling mills for lubrication and cooling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lubricating properties of emulsion liquids have been extensively studied by researchers and engineers in the field of tribology [1][2][3]. Emulsions composed of water and oil are employed as the metalworking fluid in various operations such as rolling, cutting, ironing, and grinding [1][2][3][4][5]. In steel-making industries, spray jet impingement of O/W emulsions is widely used in cold rolling mills for lubrication and cooling.…”
Section: Introductionmentioning
confidence: 99%
“…formed on the material surfaces [4] and reducing unwanted local thermal expansion/contraction of work rolls. The heat transfer characteristics of emulsion spray jets impinging on a hot solid play an important role in determining engineering demands [5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the plate-out oil film formed in a very short time, Kimura et al 10) developed the test machine shown schematically in Fig. 2.…”
Section: Conventional Plate-out Methodsmentioning
confidence: 99%
“…This theory was reported by Roberts et al 4) in the 1970s. Recently, an estimation model for oil film thickness has been proposed using a new starvation model considering the plate-out film on the roll and strip surfaces, as proposed by Inagaki et al 9) Also, Kimura et al 10) reported plate-out oil film formation on the strip surface during a very short time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from the measured results of the plate-out oil film shown in Figure 13, high plate-out efficiency is also maintained. Kimura et al 11 reported the influence of the oil droplet size on plate-out oil film. Therefore, from the point of widely control of plate-out oil film, it is important that oil droplet distribution can be controlled by air atomizing.…”
Section: Influence Of Emulsion Supply Condition On Plate-out Oil Filmmentioning
confidence: 99%